An unusual bladder mass: Dermoid cyst and review of the literature - (:unkn) unknown (My University, 2017)
0

Dermoid cysts are developmental benign anomalies and comprise at least two germ layer tissue. Dermoid cyst is usually known to be of primordial germ cell origin; however, there are some rare cases in which they have been noticed in other midline and paraxial organs. Although they generally settle in ovaries, they might be found in other tissues such as urinary bladder. Dermoid cyst should be kept in mind as a differential diagnosis for unusual presentation and histopathological appearances in bladder mass and should also be known that there is no need for further following up. We report a case of a 47-year-old woman with bladder dermoid cyst being the first case report from Turkey as a bladder mass resected endoscopically.
Keywords: Diş Hekimliği; Farmakoloji ve Eczacılık; Toksikoloji